(untitled) (Revista do Centro de Estudos Portugueses, 2014)
O ensaio examina, segundo uma perspectiva comparatista, a poesia do poeta português Herberto Helder. This paper examines, from a comparative approach, the poetry of Herberto Helder, a Portuguese poet.